The Importance of Fitness Trainer in Using Modern Technological Tools in Explosive Force Test for upper and lower parts of Football Players Field study on M’sila Teams - خوجة , باسم (sports creativity, 2025)
The Importance of Fitness Trainer in Using Modern Technological Tools in Explosive Force Test for upper and lower parts of Football Players Field study on M’sila Teams Abstract: This study aims at illustrating the Importance of Fitness Trainer in Using Modern Technological Tools in Explosive Force Test for upper and lower parts of Football Players in the training process compared to the traditional method in terms of difference coefficients and uncertainty ratios. Tests and measurements are considered as important parts to make the correct scientific decisions in the training process such as diagnosis and evaluation of training programs as well as guidance and selection. The researcher used the experimental method through the application of the explosive force test of lower and upper parts(Demi Squat) (Développé-Couché) using the MYOTEST and the classical method (1RM Demi Squat) (1RM Développé-Couché) to compare the obtained results. . The sample of the study consisted of 47 players from M’sila Teams, the results of the study were as follows: • Dispersion in modern tests is less than in traditional tests. • The use of modern technologies is more effective to assess the degree of flexibility of football players in terms of their differences compared to traditional tests. • The fundamental difference between them is in the classification of the standard levels of flexibility according to the ratios of uncertainty and dispersion and the difference coefficients